Amyloid Polymorphism in the Protein Folding and Aggregation Energy Landscape. Issue 28 (8th June 2018) - Adamcik, Jozef; Mezzenga, Raffaele
Abstract: Protein folding involves a large number of steps and conformations in which the folding protein samples different thermodynamic states characterized by local minima. Kinetically trapped on‐ or off‐pathway intermediates are metastable folding intermediates towards the lowest absolute energy minima, which have been postulated to be the natively folded state where intramolecular interactions dominate, and the amyloid state where intermolecular interactions dominate. However, this view largely neglects the rich polymorphism found within amyloid species. We review the protein folding energy landscape in view of recent findings identifying specific transition routes among different amyloid polymorphs. Observed transitions such as twisted ribbon→crystal or helical ribbon→nanotube, and forbidden transitions such helical ribbon↛crystal, are discussed and positioned within the protein folding and aggregation energy landscape. Finally, amyloid crystals are identified as the ground state of the protein folding and aggregation energy landscape. Abstract : Crystal clear : Recent studies on the protein folding energy landscape have enabled the identification of specific transition routes among different amyloid polymorphs. Amyloid crystals are a distinct polymorphic class of amyloids that are formed through the progressive untwisting and lateral aggregation of twisted ribbon amyloid fibrils, and they represent the ground state of the protein folding and aggregation energy landscape.